Integrating drivers of pro-environmental behavior and physical activity to explore (in) compatibilities between an active and an environmentally sustainable lifestyle - Eriksson, Louise; Linde, Stefan (Frontiers in Psychology, 2024)
Introduction Sport and outdoor activities have benefits on people’s health and well-being but may also increase the frequency of unsustainable behaviors. The present study explores drivers of travel mode choice and consumption of material (clothes and equipment) associated with physical activity to clarify the extent to which an active and sustainable lifestyle is compatible. The role of identity and varying levels of internalized motivation for pro-environmental behaviors (autonomous and controlled environmental motivation) and engagement in physical activity (autonomous and controlled activity motivation) was examined. In addition, socio-demographic, physical context, and life situation correlates of environmentally significant behaviors associated with physical activity were analyzed. Methods A survey of a random sample of the general public in Sweden (n = 1013) was conducted. Results After controlling for hours of physical activity, the study showed that environmental self-identity was related to a lower likelihood of using the car alone via autonomous environmental motivation and to a higher likelihood of buying and selling used material via controlled environmental motivation. Physical activity drivers displayed diverse impacts on environmentally significant behaviors, e.g., athlete identity was associated with a higher likelihood of using the car alone and buying new material, but also selling used material. Being a member of a sport or outdoor organization was related to a higher likelihood of using the car alone and buying new material, but also using active travel modes as well as buying and selling used material. Discussion With a better understanding of the drivers of environmentally significant behaviors in this domain, strategies to encourage sustainable transport and circular flows of material in sports and outdoors can be outlined.